THE ROLE OF ARTISTIC SKILLS IN YUSUF SARYOMI WORKS - Kamolova Sadoqat Jabbor qizi (Modern American Journals, 2025)
The artistic images and art skills used in the works of Yusuf Saryomi, his works, Yusuf Saryomi are illuminated on the basis of analytical thoughts.
Keywords: Yusuf Saryomi, literary heritage, literacy, creativity, creations, sufism, artistic mastery, artistic image tool, satirical work.